Fontan Circulation and Aortic Stiffness: Insights into Vascular Dynamics and Haemodynamic Interplay - Walser, Matthias; Arnold, Leonie; Mandilaras, Guido; Funk, Christoph; Dalla-Pozza, Robert; Pattathu, Joseph; Haas, Nikolaus A.; Jakob, André (Pediatric cardiology, 2025)
Increased aortic stiffness predisposes cardiac afterload and influences cardiac function. Congenital heart diseases involving aortic arch malformation and extended cardiovascular surgery, i.e. univentricular heart diseases, can lead to increased aortic stiffness. This study aimed to investigate whether Fontan patients (FO) have increased aortic stiffness within distinct aortic segments, and whether these parameters relate to Fontan-specific haemodynamics. In a prospective case–control study, 20 FO and 49 heart-transplanted control subjects with biventricular circulation underwent invasive cardiac catheterisation. We invasively measured pulse wave velocity (PWV) in the ascending aorta and along the entire aorta. Haemodynamic parameters, including end-diastolic pressure, pulmonary artery pressure, the cardiac index and systemic vascular resistance index were also assessed. FO exhibited significantly higher ascending aorta PWV (aPWV) than controls (FO: 7.2 ± 2.4 m/s|Controls: 4.9 ± 0.7 m/s, p < 0.001) and compared to the inner group central aorta PWV (cPWV; FO: 5.5 ± 1.2 m/s|Controls: 5.3 ± 1.0 m/s). Multivariate analysis confirmed this aPWV elevation in FO even after adjusting for age and BMI. aPWV and cPWV were almost identical within the control group. Correlation analyses revealed associations between cPWV and blood pressure in controls, while correlations were less apparent in FO. We detected no significant association between the aPWV and other haemodynamic parameters in any of our groups. FO exhibit increased aPWV, indicating specific vascular stiffness in the ascending aorta, while their overall aortic stiffness remains comparable to controls. Further research is needed to understand the implications of these findings on Fontan circulation and long-term cardiovascular health. Central Message Fontan patients show increased aortic arch pulse wave velocity, suggesting specific vascular stiffness. Perspective Statement Our study offers rare insights into pulse wave velocity in Fontan patients, highlighting increased arterial stiffness in the aortic arch. Vascular stiffness was particularly increased in the area of surgical reconstruction. This indicates the need for further research on vascular stiffness in Fontan circulation to understand its impact on cardiovascular health. Clinical Trial Registration German clinical trial registration, DRKS00015066.